2015
DOI: 10.1177/1352458515594042
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorders: long-term safety and efficacy of rituximab in Caucasian patients

Abstract: A fixed treatment scheme of rituximab, with re-treatment every 6 months, was efficacious for NMO and NMOSD, with a good safety profile; however, to obtain an even better benefit-risk ratio, close monitoring of CD19(+) B cells should be performed before the re-treatment of patients with high-level disability, concomitant leukopenia and hypogammaglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 33 publications
7
44
0
Order By: Relevance
“…Furthermore, Collongues et al recently described that in their cohort Body Mass Index was predictive of disability worsening on RTX, suggesting a possible impact of the dilution volume, and therefore of the effective dose, on response to RTX [22]. Few studies [10,17,[20][21][22][23][24] included patients treated with RTX-A and RTX-B, but no details of outcome measures are reported in relation to dosage regimens. Anyway, Kim et al reckon that once the disease is stabilized, less frequent RTX re-dosing might be sufficient to prevent relapses [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Collongues et al recently described that in their cohort Body Mass Index was predictive of disability worsening on RTX, suggesting a possible impact of the dilution volume, and therefore of the effective dose, on response to RTX [22]. Few studies [10,17,[20][21][22][23][24] included patients treated with RTX-A and RTX-B, but no details of outcome measures are reported in relation to dosage regimens. Anyway, Kim et al reckon that once the disease is stabilized, less frequent RTX re-dosing might be sufficient to prevent relapses [17].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, ranging from 5 to 32 patients, have been produced demonstrating the effectiveness of RTX in NMO [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Recently, a cohort of 100 NMO-SD patients treated with RTX and with a long-term follow-up (median 67 months) was described [24].…”
Section: Introductionmentioning
confidence: 99%
“…In NMO, a recent string of studies show that the repopulation of peripheral blood by B cells, especially memory B cells, coincides with clinical relapses [51,[61][62][63]. Compared with healthy controls, patients with NMO have higher serum BAFF levels, which further increases after rituximab treatment [62].…”
Section: Ms and Nmomentioning
confidence: 99%
“…Open-label studies reported a significant reduction in relapse rate and subsequent stabilization or improvement in disability as measured by expanded disability status scale scores [63,[113][114][115][116][117]. Despite improving relapse rates and reducing disease activity reduced AQP4-IgG titers are not consistently associated with clinical improvement, even after long-term B-cell depletion [118].…”
Section: Inflammatory Myopathiesmentioning
confidence: 99%
See 1 more Smart Citation